Racjonalność logiczna - Kleszcz, Ryszard (Filozofia Nauki, 1996)
The author presents an argument that the notion of rationality of beliefs must not be so restrictive as it is according to usual definitions. I.a. The postulate of effective elimination of all contradictory beliefs should be qithdrawn because nobody had the pssibility to derive and examine all the consequences of his beliefs. The final author's proposal is to enclose a kind of merely potential mechanism of elimination of contradictory beliefs into the notion concerned.